2019
DOI: 10.1002/hpm.2940
|View full text |Cite
|
Sign up to set email alerts
|

Association of maternity waiting home utilization with women's perceived geographic barriers and delivery complications in Ethiopia

Abstract: Objectives:The aim of this study is to identify the influence of perceived geographic barriers to the utilization of maternity waiting homes (MWHs) and to explore factors associated with current delivery complications among MWH users and nonusers.Methods: An observational cross-sectional study was conducted between December 2017 and June 2018 in eight health facilities with MWH in the Gurage zone of Ethiopia. The associated factors were identified by using the combination of a directed acyclic graph (DAG) conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 22 publications
6
23
3
Order By: Relevance
“…The results of the current study might be an indication that for improved MWH use, good infrastructure and awareness-creation campaigns are needed to attract women who reside in remote areas [51]. This finding, however, does not corroborate the results of previous studies conducted in Zambia [49], Gurage Zone, Ethiopia [45], and Zimbabwe [50], which found that women who stayed in MWHs were more likely to live further away from the nearest HIs.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results of the current study might be an indication that for improved MWH use, good infrastructure and awareness-creation campaigns are needed to attract women who reside in remote areas [51]. This finding, however, does not corroborate the results of previous studies conducted in Zambia [49], Gurage Zone, Ethiopia [45], and Zimbabwe [50], which found that women who stayed in MWHs were more likely to live further away from the nearest HIs.…”
Section: Discussioncontrasting
confidence: 99%
“…On the contrary, one study carried out in Gurage Zone, Ethiopia reported that pregnancy complications were not statistically associated with the MWH utilization. This might be due to the differences in the study setting, as the current study was entirely based in a rural area, where the study population might not have had alternative means to overcome the second delay but to stay at MWH [45].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the current study might be an indication that for improved MWH use, good infrastructure and awareness-creation campaigns are needed to attract women who reside in remote areas [51]. This nding, however, does not corroborate the results of previous studies conducted in Zambia [49], Gurage Zone, Ethiopia [45], and Zimbabwe [50], which found that women who stayed in MWHs were more likely to live further away from the nearest HIs.…”
Section: Discussioncontrasting
confidence: 99%
“…Many quantitative and qualitative themes emerged in this locally specific study which paralleled those in other contexts throughout the world. Others have similarly found correlation between MWH use and improvement in various measures of birth outcomes including decreases in obstructed labor [ 5 , 30 , 31 ], stillbirth [ 5 , 9 , 26 , 30 ], and uterine rupture [ 5 , 13 , 25 , 30 , 32 ], as well as higher neonatal assessment scores (e.g. Apgar) and perinatal and maternal mortality [ 26 , 30 ].…”
Section: Discussionmentioning
confidence: 99%